Wellbeing Across Occupations and in the Emergency Services: A Mixed Methods Study - Hamling, Kristen (Auckland University of Technology, 2018)
Background: Evidence indicates that emergency service work can compromise first responders’ and their families’ wellbeing. Traditionally, first responder wellbeing has been organisationally supported from a deficit perspective with interventions aimed at trauma prevention. Recently, emergency service organisations have been considering a holistic approach to first responder wellbeing. The new approach is based on evidence that health promotion yields benefits to wellbeing over illness prevention. However, there is limited evidence about factors associated with wellbeing in different occupational groups, including the emergency services. Therefore, this thesis aimed to explore wellbeing across different occupational contexts and determine how first responders experience wellbeing in the context of emergency service work. Method: This study used a sequential mixed methods research design underpinned by a pragmatist philosophy. The quantitative study used secondary data from an online survey of New Zealand workers (n = 5,126) to determine factors associated with wellbeing across different occupational contexts. The qualitative study used semi-structured interviews involving first responders and professionals who support them (n = 25) to investigate how first responders experience wellbeing. Constructivist grounded theory methods were selected for the qualitative study to explain and expand upon the quantitative findings (Charmaz, 2014). Findings: This mixed methods study revealed four key findings: (1) Wellbeing is a contextual experience, with the exception of meaning and purpose. (2) Meaning and purpose lead to wellbeing for first responders via a calling enactment. (3) Callings are difficult to achieve. (4) First responders need specific tools and skills to achieve a sense of calling. The qualitative study resulted in the construction of the heart of wellbeing theory, which for the first time contextualises wellbeing in the emergency services. Conclusion: The current study found that the experience of meaning and purpose is central to workers’ wellbeing. The data indicate that first responders experience meaning and purpose via a sense of calling. Calling enactment is difficult in the emergency services predominantly due to organisational factors, such as conflicting agendas. This research program identified that emergency service organisations need to think beyond workplace content, such as operational stress and trauma, when protecting first responder wellbeing. The evidence collected in this study indicates that there needs to be a greater emphasis on addressing first responder wellbeing via workplace context. Wellbeing interventions may be more effective if they focus more on equipping first responders to deal more effectively with workplace context so that they can experience meaning and purpose more consistently. Emergency service organisations should ensure that all first responders have access to the high leverage factors that enable them to overcome the barriers that prevent them from enacting their sense of calling. The high leverage factors identified in this study were both individually and team-oriented. Individual and team wellbeing interventions are recommended based on the current study findings.
Keywords: Wellbeing; First responders; Meaning and purpose; Calling work orientation; Contextualised wellbeing; Grounded theory; Charmaz; Pragmatism; Mixed methods methodology; Secondary data; Reflexivity; Sovereign Welleing Index